Carbon Sequestration Assesment of Mangrove Ecosystem in Karang Anyar Village, Tanggamus Regency - Kusuma, Anma Hari; Caesario, Racmad; Lahay, Almira Fardhani; Hasani, Qadar; Jati, Ciptaning Weargo; Sarida, Munti; Siregar, Amril Ma'ruf (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangroves is a ecosystem can absorb carbon more efective than teresterial vegetataion. The goal of this research is to analyze effectively carbon absorption in the mangrove aea in the Karang Anyar Village. The research was conducted in Karang Anyar Village. Survey and tree sampling were carried out from Juni to August 2024. Biomass measurements provided information on carbon sequestrtaion. Data obtained was analyzed using allometric equation. Results showed that mean carbon sequestration of the mangrove biomass in Karang Anyar Village was 40,45-69,24 kg C/m2. Carbon sink in mangrove sediment was 402,15-907,95 kg C/m2. This research showed that mangrove ecosystem in Karang Anyar Village held sufficiently high carbon stock. Nevertheless, the future study needs to be directed to carbon stock comparison with other locations in Lampung.